Improving Geoidal Height Estimates from Global Geopotential Model Using Regression Model and GPS Data - Abdullah, Khairul Anuar (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1997)
Conventionally, for most application, position of a point is often referred to the geoid as the reference surface. Thus there is an important need for the knowledge of the geoid undulation in the area where positioning tasks is performed, This requirement is made more apparent with the advent of high precision using GPS where the resulting ellipsoid height must be converted to orthometric height. An ideal solution is to use a precise gravimetric solution where the geoidal height at each GPS point is computed and applied. Unfortunately, at the moment there is no such solution available in Malaysia. However. efforts are currently being made to develop a precise gravimetric geoid, For the time being, an alternative method would have to be use and the global geopotential model is one of them. [n order to increase the accuracy of computed geoid height from the geopotential model. a regression model is used in conjunction with the GPS data. The resulting accuracy estimates of the geoid height determination increases from around 60 cm 'to about 10 cm leve1.